ANALYSIS OF THE IMPLEMENTATION OF PSAK 105 MUDHARABAH AND PSAK 106 MUSYARAKAH IN IQTISHOD UNISMA COOPERATIVE - Norma Hanifah Rosydah; Ulfi Kartika Oktaviana (IAIN Lhokseumawe, 2022)
Iqtishod UNISMA Cooperative is one of the Cooperatives that apply sharia principles in its activities. Iqtishod unisma Cooperative has several products, namely savings and financing. The purpose of this study is to find out how the application of PSAK 105 and 106 in iqtishod unisma cooperatives. This study uses a type of qualitative research by collecting data in the form of numbers, words, or images that are then reduced or summarized, after which it is presented, and finally, interpret. The data used in this study are primary and secondary. The data is using observation, interviews, and documentation. The results of this study are the recognition, measurement, presentation, and disclosure made by the Iqtishod Unisma Cooperative have not been fully by PSAK 105 Mudharabah Accounting and PSAK 106 Musyarakah. One of the causes is not following PSAK because the Iqtishod Unisma Cooperative relies on the application system and does not pay much attention to SAK standards.